2003
DOI: 10.1007/s00192-003-1071-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pelvic floor training on sexual function of treated patients

Abstract: The aim of this study was to determine the effects of improvements in urinary incontinence resulting from pelvic floor rehabilitation on the sexual function of patients. The study involved 42 clinic patients who received pelvic floor rehabilitation treatment. Their sexual histories were obtained through face-to-face interviews. Pelvic muscle strength was measured with a perineometer. Improvement in incontinence was measured with the pad test. Seventeen women reported decreased sexual desire before the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 9 publications
4
41
0
5
Order By: Relevance
“…Pelvic floor muscle exercises can improve orgasmic potential in non-orgasmic women with poor pelvic muscle tone, improve desire, performance and achievement of orgasm [43]. It should be stressed that they should be done daily for life.…”
Section: Pelvic Floor Muscle Exercisesmentioning
confidence: 99%
“…Pelvic floor muscle exercises can improve orgasmic potential in non-orgasmic women with poor pelvic muscle tone, improve desire, performance and achievement of orgasm [43]. It should be stressed that they should be done daily for life.…”
Section: Pelvic Floor Muscle Exercisesmentioning
confidence: 99%
“…‹liflki s›ras›nda idrar kaç›ran kad›nlar›n cinsel davran›fl biçimlerini inceleyen saptam›fllard›r (41) .…”
Section: Pelvik Taban Disfonksiyonu Ve Cinsel Sa¤l›kunclassified
“…Several studies have confirmed that PFME is effective in the treatment of female stress (SUI) and mixed urinary incontinence and therefore is recommended as a first-line therapy [13][14][15]. Studies also found patients who have participated in a series of pelvic floor muscle exercise experienced improvement in sexual desires [16,17].…”
Section: Exercisementioning
confidence: 99%